Healing by Creating: Patient Evaluations of Art‐Making Program. (15th March 2015) - Heiney, Sue P.; Darr‐Hope, Heidi; Meriwether, Marian P.; Adams, Swann Arp
Abstract: The benefits of using art in health care, especially with cancer patients, have been described anecdotally. However, few manuscripts include a conceptual framework to describe the evaluation of patient programs. This paper describes patients' evaluation of a healing arts program developed within a hospital for cancer patients that used art‐making, story, and therapeutic group processes to enhance emotional healing. Patients highly valued art creation, story, and group participation. The themes of the participants' open‐ended evaluations demonstrated the relevance of these three conceptual components and their merit in emotional recovery after cancer. This program evaluation lays the groundwork for future research into the therapeutic value of healing arts programs.